2022
DOI: 10.3390/ani12010125
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Fatty Acids Profile, Health Indices, and Physical Characteristics of Organic Eggs from Laying Hens at the Beginning of the First and Second Laying Cycles

Abstract: The present study compared the fatty acid profile and some physical parameters of eggs from hens reared according to the organic system at the beginning of the first and second laying cycle. A total of 1080 eggs were analysed at the beginning of the first (from the 28th to 30th week of age) and the second (from the 78th to 80th week of age) laying cycle. It was found that the hen ages influenced the egg weight, egg surface area, yolk proportion, and eggshell colour. Albumen and eggshell proportion, albumen, yo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 38 publications
(49 reference statements)
2
4
0
Order By: Relevance
“…In total, 28 FAs were identified and quantified, among which the prevalence of oleic acid (C18:1n9c) (42.45%), followed by palmitic acid (C16:0) (23.49%), linoleic acid (C18:2n6c) (8.86%), and stearic acid (C18:0) (6.64%) were observed at the initial stage of storage ( Figure 3 ). The results are consistent with those of Zita et al [ 37 ], indicating a fairly similar descending order of FA content recovered from organic eggs. As seen, storage resulted in a sharp decrease in FAs, and the percentage reduction was time and packaging type-dependent.…”
Section: Resultssupporting
confidence: 92%
“…In total, 28 FAs were identified and quantified, among which the prevalence of oleic acid (C18:1n9c) (42.45%), followed by palmitic acid (C16:0) (23.49%), linoleic acid (C18:2n6c) (8.86%), and stearic acid (C18:0) (6.64%) were observed at the initial stage of storage ( Figure 3 ). The results are consistent with those of Zita et al [ 37 ], indicating a fairly similar descending order of FA content recovered from organic eggs. As seen, storage resulted in a sharp decrease in FAs, and the percentage reduction was time and packaging type-dependent.…”
Section: Resultssupporting
confidence: 92%
“…Dalle Zotte et al [3] did not find any significant effect of production systems (cage, barn, and organic) on the above-mentioned indexes. Regarding the age-related effect, it was found that the fatty acid composition of egg yolks from late-age laying hens resulted in lower AI and TI values compared with early-age laying hens [43,45], and the detected values were in the same range of our results.…”
Section: Nutritional Indicessupporting
confidence: 86%
“…Regarding the agerelated effect, it was found that, in eggs from late-age laying hens, it was higher compared with early-age laying hens (22.3 vs. 18.2) but similar to intermediate ones (22.2) [45]. Conversely, Zita et al [43] did not find any age-related effects on the n-6/n-3 ratio during the first and second laying cycles (16.56 vs. 18.24, respectively). PUFA/SFA is a commonly used index for evaluating the nutritional value of dietary foods; it hypothesizes that all PUFAs in the diet can depress low-density lipoprotein cholesterol (LDL-C) and lower levels of serum cholesterol, whereas all SFAs contribute to high levels of serum cholesterol.…”
Section: Nutritional Indicesmentioning
confidence: 91%
See 1 more Smart Citation
“…In the late phase of laying production, due to the degradation of intestinal absorption function and the decline in antioxidant as well as immune function of laying hens lead to a decline in egg quality, resulting in huge economic losses in the poultry industry ( Feng et al, 2020 ; Dai et al, 2022 ; Zita et al, 2022 ). Dietary GML supplementation significantly affects the egg quality.…”
Section: Discussionmentioning
confidence: 99%